2011
DOI: 10.1128/jb.00532-10
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Periplasmic Chaperones Skp, SurA, and DegQ in Outer Membrane Protein Biogenesis in Neisseria meningitidis

Abstract: The periplasmic chaperones Skp, SurA, and DegP are implicated in the biogenesis of outer membrane proteins (OMPs) in Escherichia coli. Here, we investigated whether these chaperones exert similar functions in Neisseria meningitidis. Although N. meningitidis does not contain a homolog of the protease/chaperone DegP, it does possess a homolog of another E. coli protein, DegQ, which can functionally replace DegP when overproduced. Hence, we examined whether in N. meningitidis, DegQ acts as a functional homolog of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 55 publications
3
58
0
Order By: Relevance
“…S3A). Sequence alignment revealed a slightly higher identity of NgHtrA to the E. coli DegQ homolog (38%) than to DegP (37%) as recently suggested for Neisseria meningitidis (14). Hence, NgHtrA seems to be less related to other HtrAs, whereas HpHtrA and CjHtrA together with EpHtrA and SfHtrA exhibit high pairwise similarity (supplemental Fig.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…S3A). Sequence alignment revealed a slightly higher identity of NgHtrA to the E. coli DegQ homolog (38%) than to DegP (37%) as recently suggested for Neisseria meningitidis (14). Hence, NgHtrA seems to be less related to other HtrAs, whereas HpHtrA and CjHtrA together with EpHtrA and SfHtrA exhibit high pairwise similarity (supplemental Fig.…”
Section: Resultsmentioning
confidence: 83%
“…Interestingly, NgHtrA did not cleave E-cadherin, which is explainable by the structural differences in the active pocket. NgHtrA was annotated as a serine protease, but obviously revealed a higher identity to the DegQ homolog consistent with HtrA from N. meningitidis (14), suggesting that DegQ and DegP functions are similar, but do not serve as general functional homologs (14). Among other differences, the exchanged Gln-263 crucially protrudes into the pocket of NgHtrA, which might interfere with E-cadherin binding and cleavage.…”
Section: Discussionmentioning
confidence: 99%
“…NspA is a small eight-stranded ␤-barrel OMP whose correctly folded form migrates more slowly in seminative SDS-PAGE than the denatured form (18). Using this assay, we found that all NspA was folded in the ⌬GNA2091 mutant (Fig.…”
Section: Role Of Gna2091 In Omp Assemblymentioning
confidence: 93%
“…The transformants were checked by PCR for the presence of the mutant allele using primer pair NMB2090-for and NMB2092-rev and for the absence of the wild-type allele using primer pair GNA2091-for1 and NMB2092-rev. Double skp::cat⌬GNA2091, ⌬surA⌬GNA2091 and ⌬bamC⌬GNA2091 mutants were obtained by introducing the ⌬GNA2091::kan allele into previously constructed ⌬surA::cat, ⌬bamC::cat, and insertional skp::cat mutants (11,18). For complementation purposes, GNA2091 was amplified by PCR using genomic DNA of HB-1 as template and primers GNA2091-for-NdeI and GNA2091-rev-AatII.…”
Section: Methodsmentioning
confidence: 99%
“…When neisserial cell envelopes are subjected to this procedure, LptD is detected as two high molecular weight (HMW) bands, indicating that the protein is present in complexes (32) (Fig. 5A).…”
Section: Assessment Of Cell Surface Localization Of Lps-tomentioning
confidence: 99%